2015
DOI: 10.1016/j.bbacli.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Circulating long noncoding RNA GAS5 levels are correlated to prevalence of type 2 diabetes mellitus

Abstract: BackgroundDiabetes mellitus (DM), a metabolic disease, is characterized by impaired fasting glucose levels. Type 2 DM is adult onset diabetes. Long non-coding RNAs (lncRNAs) regulate gene expression and multiple studies have linked lncRNAs to human diseases.MethodsSerum samples obtained from 96 participating veterans at JAH VA were deposited in the Research Biospecimen Repository. We used a two-stage strategy to identify an lncRNA whose levels correlated with T2DM. Initially we screened five serum samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 30 publications
5
133
0
Order By: Relevance
“…For example, DANCR, SNHG3 and SNHG1 are lncRNAs that promote tumour cell proliferation in liver cancer and imply poor prognoses [54-56]; moreover, these lncRNAs exhibited tendencies towards reduced expression in response to metformin treatment in our transcriptome profile. Another lncRNA, GAS5, is positively correlated with the incidence of type 2 diabetes [57], and its down-regulation by metformin might imply a potential improvement of the metabolic condition by metformin. However, the inhibition of this lncRNA has also been demonstrated to be involved in the progression of liver fibrosis and liver cancer [58, 59].…”
Section: Resultsmentioning
confidence: 99%
“…For example, DANCR, SNHG3 and SNHG1 are lncRNAs that promote tumour cell proliferation in liver cancer and imply poor prognoses [54-56]; moreover, these lncRNAs exhibited tendencies towards reduced expression in response to metformin treatment in our transcriptome profile. Another lncRNA, GAS5, is positively correlated with the incidence of type 2 diabetes [57], and its down-regulation by metformin might imply a potential improvement of the metabolic condition by metformin. However, the inhibition of this lncRNA has also been demonstrated to be involved in the progression of liver fibrosis and liver cancer [58, 59].…”
Section: Resultsmentioning
confidence: 99%
“…GAS5 has been reported to be closely associated with various human diseases (8,28,30). GAS5 functions as a potential tumor suppressor and is downregulated in several types of cancer (28).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse lncRNA Gas5 is located on chromosome 1, with a length of 2554 bp. Recent studies have found that human serum lncRNA Gas5 level is correlated with T2DM[12]. However, it is unclear whether lncRNA Gas5 is involved in maintaining the function of adult mouse pancreatic β cells.…”
Section: Introductionmentioning
confidence: 99%